The scarcity of coins, provisional coinage, foreign coin counter-stamping and issues of the Republic, Costa Rica (1821-1848) - Vargas Zamora, José A. (2022)
Received: 15-09-2021.Approved: 09-11-2021. From colonial times to the mid XIX century the scarcity of currency, particularly that of lower denominations, was a problem in Costa Rica. As a result, cocoa seeds were authorized as money at the beginning of the 18rh century. In the 1840-decade coffee plantation labor and production became the motors of the economy and the demand for coins increased. Foreign coins were allowed to circulate to relieve the shortage. However, many were of low precious metal content or were counterfeits. British, Spanish, American, and colonial cobs were assayed and those that met the local standards of quality were engraved with seals and authorized to circulate together with locally minted pieces. The seals included figures, such as trees, a tobacco plant, a star, a lion, and young women. In this paper we provide an overview of these coins from 1821 to the foundation of the Republic in 1848 and the possible meanings of symbols engraved on them.